Attitudes and opinions of dental practitioners towards the use of clinical photography in Srinagar: a cross sectional study - Yousuf, Asif; Jan, Iram; Sidiq, Mohsin (International Journal of Research in Medical Sciences, 2020)
Background: Clinical photography has become a part of modern-day dental practice. It has been used for dento-legal documentation, diagnosis, clinical assessment, treatment planning, patient motivation, communication with the patient and laboratory, academic purposes and also for marketing. The aim of the study was to assess and determine the knowledge and the extent of the use of photography by dental practitioners of Srinagar city. Methods: A cross-sectional survey involving a questionnaire consisting of 10 questions was distributed among 88 randomly selected dental practitioners of Srinagar city, out of which 72 dental practitioners responded positively and returned the questionnaire. The data collected were computerized and analyzed statistically. The average values of the responses received by groups of questions were analyzed. Results: According to the survey conducted, 52(72.22%) dentists used photography for dental practice. Out of all the dentists surveyed, 63(87.5%) of the dentists knew about the importance of dental photography. It was observed that 40(55.55%) fresher dentists (<5 years’ experience) showed more positive attitude towards the application of photography in their dental practice. It was also revealed that the application of clinical photography among male dentists, dentists with <5 years’ experience and dentists who work with an assistant were significantly higher as compared to other dentists (p<0.05). Conclusions: Hence, from this study, majority of respondents (87.5%) were aware of the importance of dental photography. The reasons which prevented the dentist from using clinical photography were lack of time, expensive instruments, lack of interest and cross infection. Male practitioners were more likely than female practitioners to use clinical photography. Photographic training should hence be inculcated in the curriculum of dentistry. Also dental practitioners should actively participate in CDE programs on Clinical photography to improve the quality of dental practice.